Analysis of Teachers’ Perceptions of the Implementation of Early Childhood Education Assessment in Langsa City - Aulia Annisa (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study aims to analyze teachers’ perceptions of the implementation of assessment in Early Childhood Education (ECE) in Langsa City. The research focuses on teachers’ understanding of assessment, the objectives of conducting assessments, the techniques used, the alignment of assessments with children’s characteristics, the utilization of assessment results, the extent of training attended, the challenges faced, institutional support, methods of documenting assessment results, and efforts to improve assessment practices in ECE. This study employed a qualitative approach, involving three teachers in Langsa City as respondents. Data were collected through open-ended questionnaires and analyzed descriptively, complemented with tables and graphs to visualize the findings. The results indicate that most teachers perceive assessment as a process of gathering information and evaluating children’s development holistically to support the learning process. The most frequently used assessment techniques were observation, anecdotal records, interviews with children, and communication with parents. Teachers sought to align assessments with children’s characteristics through direct observation, positive interactions, and targeted questioning. Assessment results were used to adapt learning materials, design activities, and identify children’s strengths and weaknesses. However, most teachers reported insufficient training on assessment. Challenges encountered included limited time, resources, learning media, and supporting technology. Nevertheless, educational institutions were considered to provide support through supervision, provision of media, and facilities